Nutritional Status of Hospitalized Tuberculosis Patients in South Kalimantan: A Cross-Sectional Study - Mohamad Isa; Ira Nurrasyidah; Elok Hikmatun Nikmah; Desi Rahmawaty; Ali Assagaf; Haryati Haryati; Erna Kusumawardhani (Universitas Muhammadiyah Yogyakarta, 2022)
The burden of tuberculosis (TB) infection is significant in Indonesia. There is likely a substantial link between TB and malnutrition. Anemia, which is linked to TB patient outcomes and length of hospital stay, is another issue that might aggravate the disease. This study aims to identify how common undernutrition and anemia are among tuberculosis patients at the Ulin Regional Hospital in Banjarmasin. A cross-sectional observational study was conducted using medical record data from 31 hospitalized tuberculosis patients from September to December 2021. Data of weight, height, body mass index (BMI), Hemoglobin (Hb) and blood albumin level at admission were analyzed. The result showed that tuberculosis cases were mostly found in males (61.3%) aged 20-60 years (83.9%). There were 42% of patients with undernutrition (BMI 18.5), 93.5% with anemia, and 71% with hypoalbuminemia. Rifampicin resistance was found in 38.7% of all patients, with 58.3% malnutrition, 100% anemia, and 50% hypoalbuminemia. Thus, there was a possible link between tuberculosis and undernutrition condition. Screening, early diagnosis, and treatment for undernutrition, anemia, and hypoalbuminemia should be encouraged in patients with tuberculosis, whether they are susceptible or resistant to rifampicin, to lower the burden of the disease.